PERSEPSI GURU TERHADAP KEMAMPUAN SISWA KELAS V SEKOLAH DASAR DALAM MENGEMUKAKAN PENDAPAT DI KELAS - Naila Nur'Aliya; Nazwa Ramadhani; Suherli Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low ability of elementary school students to express opinions, characterized by passive behavior and lack of confidence in classroom learning. The study aims to describe teachers’ perceptions of fifth-grade students’ ability to express opinions, identify inhibiting factors, and explain teachers’ efforts to improve this ability. A descriptive qualitative approach was used through in-depth interviews with two fifth-grade teachers from two public elementary schools. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, and validated through source triangulation. The findings reveal that teachers consider the ability to express opinions an important skill, yet students’ abilities vary. Inhibiting factors include internal aspects such as self-confidence and subject comprehension, as well as external factors such as learning environment and family background. Teachers’ efforts include discussion, questioning, game-based learning, hands-on practice, and motivation. The study concludes that students’ ability is influenced by the interaction of individual, environmental, and instructional factors.